Combustion by-products and their health effects: Summary of the 16th international congress. (1st January 2021) - Violi, Angela; Cormier, Stephania; Gullett, Brian; Jansson, Stina; Lomnicki, Slawo; Luyet, Chloe; Mayer, Andreas; Zimmermann, Ralf
Abstract: The 16th International Congress on Combustion By-Products and their Health Effects (PIC2019) was held in Ann Arbor, Michigan, from July 10 to 12, 2019. For the last 28 years, this conference has served as an interdisciplinary platform for the discussion of the formation, environmental fate, health effects, policy, and remediation of combustion by-products. The technical areas for PIC2019 included mobile and stationary sources in urban environments, open fires, in- door air pollution, and halogenated pollutants. The congress was sponsored by the National Institute of Environmental Health Sciences (NIEHS), the U.S. EPA, the School of Public Health at the University of Michigan, the Civil and Environmental Engineering Department at the University of Michigan, the Mechanical Engineering Department at the University of Michigan, the Aerospace Engineering Department at the University of Michigan, and the Climate and Space Sciences and Engineering Department at the University of Michigan. Special features of the conference included a career path and round table discussion on translating research and engaging communities.